Satisfaction with support versus size of network: Differential effects of social support on psychological distress in parents of pediatric cancer patients - Harper, Felicity W. K. (Psychooncology, 2015)
OBJECTIVE: This study examined the direct and the buffering effects of social support on longer-term global psychological distress among parents coping with pediatric cancer. In both sets of analyses we examined whether these effects depended on the dimension of social support provided (i.e., satisfaction with support versus size of support network). METHOD: Participants were 102 parents of pediatric cancer patients. At study entry, parents reported their trait anxiety, depression, and two dimensions of their social support network (satisfaction with support and size of support network). Parents subsequently reported their psychological distress in 3- and 9-month follow-up assessments. RESULTS: Parents’ satisfaction with support had a direct effect on longer-term psychological distress; satisfaction was negatively associated with distress at both follow-ups. In contrast, size of support network buffered (moderated) the impact of trait anxiety and depression on later distress. Parents with smaller support networks and higher levels of trait anxiety and depression at baseline had higher levels of psychological distress at both follow-ups; for parents with larger support networks, there was no relationship. CONCLUSION: Social support can attenuate psychological distress in parents coping with pediatric cancer; however, the nature of the effect depends on the dimension of support. Whereas, interventions that focus on increasing satisfaction with social support may benefit all parents, at-risk parents will likely benefit from interventions that ensure they have an adequate number of support resources.